ANALISIS USAHA PENGOLAHAN IKAN ASIN DAN KONTRIBUSINYA TERHADAP PENDAPATAN RUMAH TANGGA NELAYAN DI KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Romita, T.; Ramli, M.; ', Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRAK   This study Held on 20 August to 4 September 2014. The aims : 1) the cost of production, sales and profits by analyzing the processing of salted fish. 2) To know how much the contributions made from salted fish processing companies to the total household income of fishermen. 3) To know the limitations and problems in the processing of salted fish processing companies. Take census respondents to the salted fish processors that perform processing each month, amounting to 2 persons, while it done in a simple random sumpling on salted fish processors do processing depending on the season less than 14 respondents. The average incurred by the salted fish processing performed per month in the first year total cost of Rp 20.463.667 with revenues of Rp 30.38 million and the average profit earned Rp 10.036.333, average total cost spent by processing salted fish depending on the season is Rp 5.380.193 with a turnover of Rp 6.536.923 and the average profit earned Rp 1,118,378. Contributions average score given by the processing of salted fish, which depend on the season amounted to 19% and which is not dependent on the processing of regular season by 81%, wherein the contribution of salted fish processing company still shows very low because of the low contribution of the low production. Problems in the processing of raw materials salted fish depending on the season, the equipment is simple, the drying process depends on the weather and lack of hygiene.     Keywords: salted fish, cost, revenue , profit , contribution